Peluang Pengembangan Limbah Batang Sawit Menjadi Papan Panel Komposit - Rindukasih Bangun; Liswar Hamid (Badań Perencanaan Pembangunan Dearth, Penelitian dań Pengembangan Provinsi Riau, 2016)
There is no utilization of waste oil palm trunks in significant numbers right now. The purpose of this study 1) to assess the potential of raw materials of oil palm trunks. 2). To create composite panel board from waste oil palm trunks. The study was conducted in three sub-districts in Kampar. Composite panel board was analyzed in the laboratory Sentra Polymers – Badan Pengkajian dan Penerapan Teknologi (BPPT). It was found that raw material potential of oil palm trunk with optimistic scenario was 8.041.220 m3. Density of composite panel boards that use phenol formaldehyde was 0,702 g/cm3, acrylic was 0.72 g/cm3 and unsaturated polyester was 0.892/cm3. Composite panel board using unsaturated polyester adhesive hadthe besthardness characteristics than the other adhesive. Composite panel board with phenol formaldehyde adhesive can be used to hold heavy loads and can be used outdoors, while the particle board with acrylic adhesive can be used indoors, and holding a lighter load.